The Mediation Impact of Customer Relationships in Influencing The Purchase Intention - Wijaya, Jason; Wiratama, Alvianto; Proboyo, Adelina (International Journal of Organizational Behavior and Policy, 2024)
The surge in social media users has instigated profound shifts in societal interactions. Brands are now compelled to prioritize customer engagement on social media to influence purchase intention, thereby boosting overall sales and revenue. This study specifically analyzed the mediating role of customer relationships in the relationship between social media marketing activities and purchase intention. The research was centered on people in Indonesia who have seen Tokopedia’s Instagram content. Employing a simple random sampling approach, a questionnaire was disseminated, and subsequently, the PLS-SEM method was applied to evaluate the responses from 119 valid participants. The results showed a notable impact of social media marketing activities on purchase intention and a significant correlation between customer relationships and purchase intention. Additionally, the findings suggest that customer relationships partially mediate the connection between social media marketing activities and purchase intention.